2017
DOI: 10.1155/2017/8683970
|View full text |Cite
|
Sign up to set email alerts
|

Dental Age and Tooth Development in Orthodontic Patients with Agenesis of Permanent Teeth

Abstract: Objective. To compare the development of permanent teeth in a group of children with the congenitally missing permanent teeth (CMPT) and corresponding nonaffected group. Methods. The formation stages of all developing permanent teeth were determined on 345 panoramic radiographs (OPTs) by the method of Haavikko (1970), and dental age was calculated. The paired samples t-test was used to compare the differences between dental age (DA) and chronological age (CA) in those with CMPT and those not affected. Spearman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
2
12
0
1
Order By: Relevance
“…The appropriate timing for the optimal orthodontic treatment approach depends on the localization and number of congenitally missing teeth, age, skeletal and dental characteristics of the patient as well as available finances and patient motivation ( 31 , 32 ). Clinical problems faced in treating CMPT patients embrace amount of space, aligning teeth, deep overbite and the final retention ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate timing for the optimal orthodontic treatment approach depends on the localization and number of congenitally missing teeth, age, skeletal and dental characteristics of the patient as well as available finances and patient motivation ( 31 , 32 ). Clinical problems faced in treating CMPT patients embrace amount of space, aligning teeth, deep overbite and the final retention ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypodontia is more common in females [ 10 , 11 ]. Badrov et al reported that dental development was more delayed in children with congenitally missing permanent teeth than in the control group [ 12 ]. Hyperdontia is diagnosed if supernumerary teeth are present.…”
Section: Introductionmentioning
confidence: 99%
“…They found that patients had a shorter posterior facial height in the mixed dentition, but no significant differences in the permanent dentition, compared with the control group. However, it is difficult to evaluate patients with oligodontia according to dental age because dental age is based on the timing of eruption of permanent teeth [ 25 ]. Thus, alternative, yet objective, evaluation methods are necessary for patients with oligodontia.…”
Section: Introductionmentioning
confidence: 99%